1984
DOI: 10.1002/1097-0142(19840115)53:2<311::aid-cncr2820530222>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mixed müllerian tumors of the uterus

Abstract: One hundred and eight patients with a diagnosis of malignant mixed müllerian tumors of the uterus treated at the M.D. Anderson Hospital from 1948 through 1977 were analyzed. Pathology was reviewed and subdivided according to the sarcomatous element. No difference in pattern of recurrence or survival could be demonstrated between homologous, heterologous, or undifferentiated sarcomatous elements. Nine patients were treated with only palliative intent due to advanced local disease combined with poor medical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…6,46 Finally, and most compellingly, the age of the patients, the low stage of most of the tumors, and the generally favorable prognosis of the tumors support that they are a variant of EC rather than MMMT, tumors that usually occur in older patients 1,14 who often have high-stage disease 29,30,40 and a fatal outcome. 4,9,19,21,22,25,44,45 In addition to MMMTs, the differential diagnosis of CHECs includes sertoliform ECs, low-grade endometrial stromal sarcomas (LGESS) with sex cord-like patterns, and uterine tumors resembling ovarian sex cord tumors (UTROSCTs). The rare sertoliform ECs 20,48 have focal to predominant patterns resembling ovarian Sertoli cell tumors, being characterized by small, hollow tubules lined by columnar cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,46 Finally, and most compellingly, the age of the patients, the low stage of most of the tumors, and the generally favorable prognosis of the tumors support that they are a variant of EC rather than MMMT, tumors that usually occur in older patients 1,14 who often have high-stage disease 29,30,40 and a fatal outcome. 4,9,19,21,22,25,44,45 In addition to MMMTs, the differential diagnosis of CHECs includes sertoliform ECs, low-grade endometrial stromal sarcomas (LGESS) with sex cord-like patterns, and uterine tumors resembling ovarian sex cord tumors (UTROSCTs). The rare sertoliform ECs 20,48 have focal to predominant patterns resembling ovarian Sertoli cell tumors, being characterized by small, hollow tubules lined by columnar cells.…”
Section: Discussionmentioning
confidence: 99%
“…The 31 patients ranged in age from 25 to 83 years (mean, 52 years). The proportion within each stage were as follows: stage Ia, 9.7%, stage Ib, 45.2%, stage Ic, 9.7%, stage IIb, 16.1%, stage IIIc 3.2%, and stage IV, 3.2%. In 4 patients (12.9%), staging information was not available.…”
mentioning
confidence: 99%
“…Carcinosarcoma is a rare, aggressive tumor with a poor prognosis and consists of both carcinoma and sarcoma components [1][2][3]. We previously completed a retrospective study on factors affecting the prognosis of carcinosarcoma, endometrial stromal sarcoma, and leiomyosarcoma [4], and reported that chemotherapy did not significantly predict overall survival for endometrial stromal sarcoma (p = 0.0714) or leiomyosarcoma (p = 0.989).…”
Section: Introductionmentioning
confidence: 99%
“…4 The 5-year survival rate has been estimated to be between 30% and 40%. 5,6 The common sites of recurrence or metastasis are the lung and abdomen, constituting nearly 60% in one series besides local and regional spread. 3 Duodenal malignancies as a whole are a rare occurrence, and sarcomas constitute only 6% of these tumors.…”
Section: Discussionmentioning
confidence: 99%